Synopsis of the Neotropical Premnobiina (Coleoptera: Curculonidae: Scolytinae: Ipini) with descriptions of new species, new synonymy and keys to species - Atkinson, Thomas H.; Flechtmann, Carlos A.H. [UNESP]; Petrov, Alexander V. (Magnolia Press, 2023)
One new species of Neotropical Premnobius Eichhoff is described: P. brownei Atkinson & Flechtmann from Brazil. The presence of the related genus Premnophilus Browne is confirmed from South America and six new species are described: P. bertii Atkinson & Flechtmann from Brazil, P. jordali Petrov from Peru, P. maiai Atkinson & Flechtmann from Brazil, P. pedrosai Atkinson & Flechtmann from Brazil, P. sarahsmithae Atkinson & Flechtmann from Brazil and Trinidad and Tobago, and P. wilsoni Atkinson & Flechtmann from Brazil. French Guiana, and Peru. Gnathotrupes megapunctatus Bright, 2019 is recognized as a synonym of Premnobius perezdelacruceii Petrov & Atkinson, 2018. A synopsis of previously described Premnobius species and keys to species in both genera are presented. Generic characters for the three genera of Neotropical Ipini are discussed.
Keywords: Acanthotomicus; generic characters; Premnobius; Premnophilus; South America; taxonomy